ANALISIS PRODUKTIVITAS INDUSTRI PENGOLAHAN BESAR-SEDANG NON MINYAK DAN GAS DI INDONESIA (PENDEKATAN TOTAL FACTOR PRODUCTIVITY) - Muhammad Basorudin; Dwi Rizky Syaifullah; Aisyah Puteri Utama (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2020)
Growth in Total Factor Productivity in Indonesia shows a trend showing a slowing trend, even negative during the 1990-2015 period. This indicates that industries in Indonesia are vulnerable to crisis shocks. Therefore, the purpose of this study is to determine the TFP condition of the non-oil and gas industry in Indonesia and to find out what factors influence it. This research uses the Solow Model and the Cobb Douglas Model with REM (Random Effect Model) analysis technique. This is because the number of series is less than the number of individuals. The conclusion that can be drawn from this study is the condition of Indonesia's TFP grew by an average of 3.6% for all industry sectors. Then, the factors that significantly influence output are Input Costs, Number of Labor, TFP, and Dummy Variables (crisis of 2013).